Prospection of genomic regions divergently selected in racing line of Quarter Horses in relation to cutting line - Meira, Camila Tângari [UNESP]; Curi, Rogerio Abdallah [UNESP]; Farah, M. M. [UNESP]; Oliveira, H. N. de [UNESP]; Beltran, N. A. R. [UNESP]; Silva, J. A. Ii V. [UNESP]; Mota, M. D. S. da [UNESP] (Cambridge Univ Press, 2014)
Selection of Quarter Horses for different purposes has led to the formation of lines, including racing and cutting horses. The objective of this study was to identify genomic regions divergently selected in racing line of Quarter Horses in relation to cutting line applying relative extended haplotype homozygosity (REHH) analysis, an extension of extended haplotype homozygosity (EHH) analysis, and the fixation index (F-ST) statistic. A total of 188 horses of both sexes, born between 1985 and 2009 and registered at the Brazilian Association of Quarter Horse Breeders, including 120 of the racing line and 68 of the cutting line, were genotyped using single nucleotide polymorphism arrays. On the basis of 27 genomic regions identified as selection signatures by REHH and FST statistics, functional annotations of genes were made in order to identify those that could have been important during formation of the racing line and that could be used subsequently for the development of selection tools. Genes involved in muscle growth (n = 8), skeletal growth (n = 10), muscle energy metabolism (n = 15), cardiovascular system (n = 14) and nervous system (n = 23) were identified, including the FKTN, INSR, GYS1, CLCN1, MYLK, SYK, ANG, CNTFR and HTR2B.
Keywords: equine; fixation index; extended haplotype homozygosity; selection signature; SNP array